2016
DOI: 10.1128/jvi.02783-15
|View full text |Cite
|
Sign up to set email alerts
|

Mononucleated Blood Cell Populations Display Different Abilities To Transmit Prion Disease by the Transfusion Route

Abstract: Previous experiments carried out in a sheep scrapie model demonstrated that the transfusion of 200 l of prion-infected whole blood has an apparent 100% efficacy for disease transmission. These experiments also indicated that, despite the apparent low infectious titer, the intravenous administration of white blood cells (WBC) resulted in efficient disease transmission. In the study presented here, using the same transmissible spongiform encephalopathy (TSE) animal model, our aim was to determine the minimal num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…4 It has also been demonstrated that intravenous infusion of white blood cell (WBC) products from preclinical scrapie-infected sheep can spread TSE, with a minimum pathogenic titre of 10 5 WBCs or 100 μL of whole blood, lower than previous leukoreduction standards for red blood cell (RBC) concentrates in transfusion medicine. 5 These findings indicate that the host immune system can play a significant role in the invasion and transmission of TSE. PrP C , encoded by the PRNP gene and consisting of approximately 250 amino acid residues, is a highly conserved membrane-bound glycoprotein anchored by glycosylphosphatidylinositol (GPI).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…4 It has also been demonstrated that intravenous infusion of white blood cell (WBC) products from preclinical scrapie-infected sheep can spread TSE, with a minimum pathogenic titre of 10 5 WBCs or 100 μL of whole blood, lower than previous leukoreduction standards for red blood cell (RBC) concentrates in transfusion medicine. 5 These findings indicate that the host immune system can play a significant role in the invasion and transmission of TSE. PrP C , encoded by the PRNP gene and consisting of approximately 250 amino acid residues, is a highly conserved membrane-bound glycoprotein anchored by glycosylphosphatidylinositol (GPI).…”
Section: Introductionmentioning
confidence: 90%
“…While it was generally believed that the effects of TSE were limited to the central nervous system (CNS); subsequent studies have demonstrated that PrP Sc primarily aggregates and replicates in the secondary lymphoid organs (SLOs) during host invasion, after which they migrate to the CNS . It has also been demonstrated that intravenous infusion of white blood cell (WBC) products from preclinical scrapie‐infected sheep can spread TSE, with a minimum pathogenic titre of 10 5 WBCs or 100 μL of whole blood, lower than previous leukoreduction standards for red blood cell (RBC) concentrates in transfusion medicine . These findings indicate that the host immune system can play a significant role in the invasion and transmission of TSE.…”
Section: Introductionmentioning
confidence: 99%
“…In sheep transfused with blood components from BSE‐infected donor sheep, the highest transmission rates were found in those inoculated with buffy coat fractions . In the sheep scrapie model, the minimum number of white blood cells capable of transmitting scrapie following intravenous administration was 10 5 . The distribution of infectivity among specific subsets of WBC (e.g.…”
Section: Animal Studiesmentioning
confidence: 99%
“…The distribution of infectivity among specific subsets of WBC (e.g. lymphocytes, monocytes, granulocytes) has not been clearly established, but all these cell types may be capable of transmitting infection to varying extents .…”
Section: Animal Studiesmentioning
confidence: 99%
“…The primary driver for the maintenance of the vCJD policies is a theoretical concern for a genetically at-risk population who may develop the condition at a later time, harboring infectious prions in lymphatic tissues (Wilson and Ricketts 2006a). There is no blood or urine test for the identification of vCJD, although this remains an area of active research interest (Edgeworth et al 2011;Moda et al 2014;Douet et al 2016).…”
Section: Donor Deferral Of Individuals With Vcjd Risk Factors-mentioning
confidence: 99%